Antropologi Maritim : Inovasi,Budaya dan Identitas di Wilayah Laut dan Pesisir - Muhammad Nawir; Nabilah Lutfiyyah; Fasikul Ikhsan; Mustika Mustika (Universitas Palan, 2024)
This research holistically explores the role of innovation, cultural heritage, and identity in the context of maritime anthropology. The focus on fishing technology, cultural practices, and the influence of globalization provides a profound understanding of the dynamics of coastal community life. The research findings also identify interactions among communities, comprehending knowledge exchange and adaptation to sustain cultural heritage and innovation. Additionally, the inclusion of contributions from previous research enriches the understanding of community participation in coastal development programs. These findings establish a solid foundation for the preservation of cultural heritage and a deep understanding of coastal community life.